2003
DOI: 10.1080/09553000310001636639
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose radiotherapy (LD‐RT) and the modulation of iNOS expression in adjuvant‐induced arthritis in rats

Abstract: The clinically and histologically observed prevention of the progression of adjuvant arthritis after LD-RT given during the peak of the acute inflammatory response and the reduction of cartilage and bone destruction in the chronic phase appears to be related to the modulation of iNOS activity by low X-ray doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 19 publications
6
45
0
Order By: Relevance
“…Many of these effects persisted at 9 months. Our results are in accordance with some reports showing the anti-inflammatory effect of low-dose irradiation [51,61] and of low dose radiotherapy (<1Gy or fractionated) [62][63][64].…”
Section: Discussionsupporting
confidence: 83%
“…Many of these effects persisted at 9 months. Our results are in accordance with some reports showing the anti-inflammatory effect of low-dose irradiation [51,61] and of low dose radiotherapy (<1Gy or fractionated) [62][63][64].…”
Section: Discussionsupporting
confidence: 83%
“…In subsequent decades, these characteristics were confirmed in a variety of inducible inflammatory models in rabbits, rats, and, more recently, in human tumor necrosis factor α(TNF-α) transgenic mice [19]. These models convincingly indicate that low-dose irradiation inhibits proliferation of synovial cells and synthesis of synovial fluid, reduces the destruction of cartilage and bone, hampers expression of iNOS and IL-1, and increases secretion of the anti-inflammatory cytokine TGF-β1 concomitant with an increased expression of heat shock protein 70 (Hsp70) and heme oxygenase-1 (HO-1; [3,8,18,26,54,59]). Notably, very recent in vitro data confirmed an inhibition of IL-1β-induced catenin signaling by LD-RT, with subsequent suppression of the sex-determining region Y-box 9 (Sox-9) transcription factor and NF-κB pathways in articular chondrocytes, which may well contribute to the palliation of pathophysiological processes in cartilage disorders [30].…”
Section: Preclinical Modelsmentioning
confidence: 99%
“…Namely, these were single doses of 0.3-1.0 Gy in 4-5 fractions for acute and 1-3 fractions for chronic diseases per week to total doses of 3-5 Gy and 12 Gy, respectively (Seegenschmiedt et al, 1997). In animal studies, there are reports that indicated the anti-inflammatory effect and the reduction of clinical symptoms if the local irradiations were given with daily fractionated doses of 5 x0.5 Gy, total dose was 2.5 Gy (Hildebrandt et al, 2000(Hildebrandt et al, , 2003. In Nakatsukasa et al's reports (2008Nakatsukasa et al's reports ( , 2010, the whole body irradiation was conducted, therefore somewhat higher doses than that of local irradiation might be applied.…”
Section: Foxp3mentioning
confidence: 99%
“…Therefore the authors of our referenced papers might take clinically low dose irradiation into consideration because they finally aimed to develop new therapies for above diseases. Moreover, there are some reports that investigated the mechanism of LD-RT using the animal models (Hildebrandt et al 2000(Hildebrandt et al , 2003Rödel et al 2007). 0.5 Gy/exposure of γ-or x-ray irradiation was also regarded as low-dose in these animal studies.…”
Section: Introductionmentioning
confidence: 99%